Get started in shares : trading for the first-time investor - Arnold, Glen (Pearson, 2013)
Investing can be fun as well as rewarding. It could certainly earn you much more than you could gain by sticking your money in a bank account. It really does not require much to make money from the stock market - just an understanding of a few simple concepts and the following of a few rules. Written by the UK's most successful writer on investing, Get Started in Shares explains in very clear and simple terms what shares are, how they are traded and what to look out for as an owner of shares. This is a straight-talking guide to the mysteries of investing that assumes no prior knowledge a.